SALSA: A Regulator of the Early Steps of Complement Activation on Mucosal Surfaces - Reichhardt, Martin Parnov; Meri, Seppo (Frontiers in Immunology, 2016)
Complement is present mainly in blood. However, following mechanical damage or inflammation, serous exudates enter the mucosal surfaces. Here the complement proteins interact with other endogenous molecules to keep microbes from entering the parenteral tissues. One of the mucosal proteins known to interact with the early complement components of both the classical and the lectin pathway, is the salivary scavenger and agglutinin (SALSA). SALSA is also known as DMBT1 (deleted in malignant brain tumors 1) and gp340. It is found both attached to the epithelium and secreted into the surrounding fluids of most mucosal surfaces. SALSA has been shown to bind directly to C1q, mannose binding lectin (MBL) and the ficolins. Through these interactions SALSA regulates activation of the complement system. In addition, SALSA interacts with surfactant proteins A and D, secretory IgA and lactoferrin. Ulcerative colitis and Crohn’s disease are examples of diseases, where complement activation in mucosal tissues may occur. This review describes the latest advances in our understanding of how the early complement components interact with the SALSA molecule. Furthermore, we discuss how these interactions may affect disease propagation on mucosal surfaces in immunological and inflammatory diseases.